2020
DOI: 10.3390/w12051277
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Differentiation and Multiannual Dynamics of Water Conductivity in Lakes of the Suwałki Landscape Park

Abstract: Water conductivity in 23 lakes of the Suwałki Landscape Park (SLP) was tested in the years 2012–2014. Conductivity profiles were made at the deepest place every two months between spring and autumn water mixing. The collected measurement data, supplemented with historical data, were used to identify factors that shape the spatial variability of water conductivity and to reconstruct its multiannual changes. The range of variability of the mean conductivity of surface water of the SLP lakes ranged from 178 to 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For example, wind mixing is more intense during these seasons and can lead to the release of phosphorus and nitrogen from the sediments, a process which favors eutrophication [59]. In addition, based on the sensitivity analysis results, it is concluded that the EC parameter role is not easy to be understood, since it is associated with complex processes such as wind mixing and inorganic dissolved matter inflow from the lake's catchment, e.g., surface runoff and river inflow [60]. Nevertheless, the ANN managed to associate the increased levels of EC with elevated algal production, which possibly shows the effect of increased nutrients on the algal productivity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, wind mixing is more intense during these seasons and can lead to the release of phosphorus and nitrogen from the sediments, a process which favors eutrophication [59]. In addition, based on the sensitivity analysis results, it is concluded that the EC parameter role is not easy to be understood, since it is associated with complex processes such as wind mixing and inorganic dissolved matter inflow from the lake's catchment, e.g., surface runoff and river inflow [60]. Nevertheless, the ANN managed to associate the increased levels of EC with elevated algal production, which possibly shows the effect of increased nutrients on the algal productivity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the presence of other ions such as Fe3 +, Fe2 +, Mn2 +, Al3 +, NO3-, HPO4-, H2PO4-, if these ions are not present in large quantities in water, does not affect the electrical conductivity. The reliability of estimating the composition of mineral salts by electrical conductivity is largely affected by the temperature and unequal conductivity of different salts [3,4,10].…”
Section: Electrical Conductivity Of Watermentioning
confidence: 99%
“…To determine the average estimate of mineralization, the following empirically found ratio can be followed as the amount of salt (mg / l) = 0.65 mS / cm That is, the measured conductivity is multiplied by 0.65 to determine the salt content. In fact, the value of this coefficient varies between 0.55 ÷ 0.75 depending on the type of water [1,3,4]. NaCl content (mg / L) = 0.53 mS / cm or 1 mg / L NaCl provides a conductivity of 1.9 mS / cm.…”
Section: Electrical Conductivity Of Watermentioning
confidence: 99%
See 1 more Smart Citation
“…The conductivity was below the optimum range of 200-1,000 uS/cm (Fleming, 2019) that is suitable for most aquatic organisms. In case of Luetshokha lake, low conductivity indicated that the water is not contaminated by inorganic pollutants or run off from the sorrounding catchment area (Borowiak et al, 2020).…”
Section: Physico-chemical Variables Of Luetshokha Lake Watermentioning
confidence: 99%